Coexistence of Merons with Skyrmions in the Centrosymmetric Van Der Waals Ferromagnet Fe5–xGeTe2 (Adv. Mater. 17/2023). Issue 17 (26th April 2023) - Casas, Brian W.; Li, Yue; Moon, Alex; Xin, Yan; McKeever, Conor; Macy, Juan; Petford‐Long, Amanda K.; Phatak, Charudatta M.; Santos, Elton J. G.; Choi, Eun Sang; Balicas, Luis
Abstract : 2D Magnets In article number 2212087, Luis Balicas and co‐workers investigate topological spin structures detected in Fe5− x GeTe2, or the coexistence of planar spin vortices containing merons at their center with skyrmions. Their simulations reveal that the coexistence of merons with skymions originates from regions of in‐plane and out‐of‐plane magnetic anisotropy, respectively.